Comparative study of the effect of different temperatures on bovine bone used for bone repair of critical calvaria defects in rats - Egas, Lais Sara [UNESP]; Matsumoto, Mariza Akemi [UNESP]; Hadad, Henrique [UNESP]; Tonini, Karen Rawen [UNESP]; de Weert, Daniela Atili Brandini [UNESP]; Perri de Carvalho, Paulo Sérgio; Ponzoni, Daniela [UNESP] (Wiley, 2023)
To evaluate the osteoconductive potential of inorganic biomaterials of bovine origin submitted to different temperatures in the bone repair of critical defects in rat calvaria. Forty-eight rats were divided into four groups according to the material used to fill the defect: control group (GC), the defect was filled only with blood clot (n = 12); GBO, defect filled with Bio-Oss®, deproteinzed at 300°C (n = 12); GOX, defect filled with Inorganic GenOx®, deproteinzed from 850 to 1200°C (n = 12) and G700, defect filled with Inorganic GenOx 700, deproteinzed at 700°C (n = 12). In each animal's calvaria, a trephine bur with 5 mm internal diameter was used to produce a 6 mm-diameter central defect. Gen Derm® resorbable bovine membrane was superimposed over all defects. Subsequently, animals were euthanized at 30 and 60 days after surgery. The pieces were sent for histological and histometric analysis to evaluate the following variables: bone neoformation, presence of biomaterial, mononuclear and polymorphonuclear leukocytes, presence of other tissues (granulation and medullary) and maturation of collagen fibers. The most representative group for bone neoformation was GC. At 30 days, there was a higher mean of mature bone tissue (75.8). At 60 days, there was no statistical difference between the GC (64.9), GBO (32.9), GOX (45.3), and G700 (26.6) groups. GBO presented the highest amount of biomaterial after 30 days (115.9) and 60 days (118.5). All bovine biomaterials were biocompatible and osteoconductive. GOX promoted the best bone repair of the studied materials.
Keywords: biocompatible materials; bone regeneration; models animal